Rules of origin in ASEAN : a way forward - Inama, Stefano; Sim, Edmund W. (Cambridge, UK : Cambridge University Press, 2015)
'Rules of Origin in ASEAN is the first in-depth exploration of the complex rules of origin in ASEAN's trade agreements. Written by two leading practitioners, they explain with clarity the existing ASEAN Rules of Origin (RoO) practices and their administration regimes in a comparative context and provide a recommendation for reform. The ASEAN RoOs can be simplified by focusing on value of materials and lowering the regional value content required to qualify as ASEAN-origin. The administration of ASEAN RoOs can be improved by expanding the use of self-certification, moving away from document-based verification to more modern post-entry audit and trade facilitation approaches. This is a timely and important topic which will be insightful to practitioners, policymakers and businesses in understanding how commerce and trade is conducted in Southeast Asia'--
Machine generated contents note: 1. Introduction; 2. The initial set of ASEAN rules of origin: the lack of clarity and transparency masqueraded as simplicity, 1992-5; 3. Externalizing the confusion: the proliferation of rules in the ASEAN FTAs with dialogue partners; 4. The silent cost: the cumbersome administration of ASEAN rules of origin; 5. The possible way forward: self-certification; 6. Conclusion and recommendations; Executive summary; Appendices; Index.
Includes bibliographical references and index.
Keywords: ASEAN; Certificates of origin -- Southeast Asia; Tariff -- Law and legislation -- Southeast Asia